Extent of bioleaching and bioavailability reduction of potentially toxic heavy metals from sewage sludge through pH-controlled fermentation - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ; YEŞİL, HATİCE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Utilization of anaerobically stabilized sewage sludge on arable lands serve as a renewable alternative to chemical fertilizers as it enables recycling of valuable nutrients to food chain. However, probable pres-ence of heavy metals in sewage sludge restricts the use of stabilized sludge on lands. In this study, a novel approach based on pH-controlled fermentation and anaerobic metal bioleaching was developed to reduce ecotoxicity potential of fermented sludge prior to its land application. Sewage sludge was sub-jected to pH-controlled fermentation process at acidic, neutral, and alkaline pH levels with the aim of increasing metal solubilization and decreasing bioavailable metal fractions through anaerobic bioleaching. Alkaline reactor performed the best among all reactors and resulted in 3-fold higher hydrolysis (34%) and 6-fold higher acidification (19%) efficiencies along with 43-fold (in average) higher metal solubiliza-tion than that of neutral pH reactor. As a result of alkaline fermentation, 32-57% of the metals remained as bioavailable and 34-59% of the metals were encapsulated as non-bioavailable within solid fraction of fermented sludge (biosolid), whereas 8-12% of total metal was solubilized into fermentation liquor. Our results reveal that anaerobic bioleaching through alkaline fermentation enables biosolid production with less metal content and low bioavailability, facilitating its utilization for agricultural purposes. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Alkaline fermentation; Dissolved organic matter; Metal solubilization; Volatile fatty acids; Waste activated sludge; WASTE ACTIVATED-SLUDGE; FATTY-ACIDS ACCUMULATION; ANAEROBIC-DIGESTION; MICROBIAL COMMUNITY; BIOGAS PRODUCTION; ALKALI TYPES; STABILIZATION; FRACTIONATION; ACIDIFICATION; DEGRADATION